Wafer-scale heteroepitaxy GaN film free of high-density dislocation region with hexagonal 3D serpentine mask - Menglai Lei; Huanqing Chen; Muhammad Saddique Akbar Khan; Shukun Li; Rui Lang; Peijun Wen; Guo Yu; Shengxiang Jiang; Hua Zong; Xiaodong Hu (Applied Surface Science Advances, 2023)
GaN-based III-Nitride compound semiconductors are fundamental materials for high-performance optoelectronic and electronic devices. Low-defect-density substrate has been a major bottleneck in achieving high internal quantum efficiency and high breakdown voltage in those devices. However, a large-scale and uniform low dislocation density GaN film is still hard to obtain on foreign substrates, which is the mainstream economical method in scientific research and industrial production. Here, we present a 3D serpentine mask method of growing high-quality GaN film on foreign substrates without high dislocation density (HDD) areas by designing both sectional and planar shapes of stacked masks. The serpentine channel in the cross-section mechanically blocks the extended dislocations and the hexagonal planar pattern reduces the dimension of coalescence geometry. A wafer-scale GaN epilayer, free of HDD zone, with the overall threading dislocation density of 1.7 × 107 cm−2 estimated by plan-view cathode luminescence, is achieved in the metal-organic chemical vapor deposition system. Then, an array of light-emitting diodes based on this substrate with low forward voltages and high light output powers are fabricated, which introduces a practical method to provide high-quality GaN films for high-performance optoelectronic devices.